Population Status and Distribution of Himalayan Brown Bear (Ursus arctos isabellinus) in Musk Deer National Park Neelum, Azad Jammu and Kashmir (Pakistan): Himalayan Brown Beer Population Study - Ali, Usman; Iftikhar, Naeem; Shafi, Nuzhat; Ahmad, Khawaja Basharat; Awan, Muhammad Siddique; Minhas, Riaz Aziz; Khan, Liaqat Ali (Biological Sciences - PJSIR, 2018)
The Himalayan brown bear (Ursus arctos isabellinus) is considered as .Endangered. in Pakistan. However, a small population of this species still exists in northern Pakistan including Azad Jammu and Kashmir (AJK). A study was conducted to determine population status and distribution of Himalayan brown bear in Musk Deer National Park (MDNP), from April 2011 to September 2012. MDNP, covering an area of 528.16 km2, is situated in the extreme north of AJ&K (upper Neelum Valley) about 155 km away from Muzaffarabad. Study area was divided into three zones (Phulawai, Sardari and Loser) and searched for brown bear signs and evidences. A total of 17 transect surveys were carried out to collect the data on current population status and distribution of Himalayan brown bear in the study area. In addition, questionnaires based surveys were carried out in the area to gather maximum information about this species. Based on direct and indirect signs collected, a total population of about 12 individuals with a population density of 0.42 bear/km2 was estimated in the MDNP with maximum (0.45 bear/km2) in Loser and minimum (0.37 bear/km2) in Phulawai zone. Altitudinal preference was recorded highest (0.46 bear/km2) at the elevation level of >3000 m asl. For the proper management and conservation of Himalayan brown bear, more comprehensive study should be carried out throughout its potential habitat.